Element composition of solid airborne particles deposited in snow in the vicinity of gas-fired heating plant; Proceedings of SPIE; Vol. 10035 : Atmospheric and Ocean Optics: Atmospheric Physics - Talovskaya A. V. Anna Valerievna; Yazikov Y. G. Yegor (Egor) Grigoryevich; Filimonenko E. A. Ekaterina Anatolievna; Samokhina N. P. Nataljya Pavlovna; Shakhova T. S. Tatiana Sergeevna; Parygina I. A. Irina Alekseevna (Optical Investigation of Atmosphere and Ocean, 2016)
Title screen